2008
DOI: 10.1164/rccm.200711-1644oc
|View full text |Cite
|
Sign up to set email alerts
|

ORMDL3 Gene Is Associated with Asthma in Three Ethnically Diverse Populations

Abstract: Our results confirm that the ORMDL3 locus is a risk factor for asthma in ethnically diverse populations. However, inconsistent SNP-level results suggest that further studies will be needed to determine the mechanism by which ORMDL3 predisposes to asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
180
3
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(198 citation statements)
references
References 34 publications
(27 reference statements)
14
180
3
1
Order By: Relevance
“…However, after adjusting for the effect of rs7216389-T, association with other markers was nonsignificant. Two recent studies found no significant association of rs7216389-T with asthma in African-American patients, 10,42 which, given the difference in LD structure in European and African Americans, suggests that rs7216389-T is not the causal variant itself and that the causal variant is in lower LD with rs7216389-T in African Americans. Recently, other SNPs highly correlated with rs7216389 were found to be associated with Crohn's disease (rs2872507) 43 and type I diabetes (rs2290400), 44 indicating that sequence variants at the 17q21 locus may be involved in mechanisms regulating immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…However, after adjusting for the effect of rs7216389-T, association with other markers was nonsignificant. Two recent studies found no significant association of rs7216389-T with asthma in African-American patients, 10,42 which, given the difference in LD structure in European and African Americans, suggests that rs7216389-T is not the causal variant itself and that the causal variant is in lower LD with rs7216389-T in African Americans. Recently, other SNPs highly correlated with rs7216389 were found to be associated with Crohn's disease (rs2872507) 43 and type I diabetes (rs2290400), 44 indicating that sequence variants at the 17q21 locus may be involved in mechanisms regulating immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…macrophage | eosinophil M offatt et al (1) were the first to report in 2007 a genomewide association study (GWAS) of asthma, which demonstrated that multiple markers on chromosome 17q21 (linked to the gene orosomucoid like 3; ORMDL3) were strongly and reproducibly associated with asthma in three different asthma cohorts. The identification of ORMDL3 as an asthma-associated gene has been confirmed in additional GWAS studies and in genetic association studies in populations of diverse ethnic backgrounds (2)(3)(4). In addition to the association of ORMDL3 with asthma, it is also associated with childhood onset of asthma (1) and exposure of children with asthma to environmental tobacco smoke (2).…”
mentioning
confidence: 83%
“…Furthermore, it has been found that polymorphisms in all three ORMDL genes are associated with asthma and that asthmatics exhibit increased ORMDL levels (25). The findings on the role of ORMDL3 in asthma were replicated in studies from different populations (26)(27)(28) (Table 1). Further analyses supported the conclusion that genetic elements regulating ORMDL3 expression (Table 2) may contribute to asthma development (7,13,22,25,(29)(30)(31)(32)(33)(34).…”
Section: Association Of Ormdl3 With Asthma and Other Pathologiesmentioning
confidence: 88%
“…Yu and coworkers found that in Chinese population rs7216389 asthmatic children exhibit increased levels of IgE (38). On the other hand, several other studies examining different populations found no significant differences in the IgE levels between patients with asthma and healthy controls (28,39,40).…”
Section: Association Of Ormdl3 With Asthma and Other Pathologiesmentioning
confidence: 98%